REPRODUCTIVE BIOLOGY OF THE FEMALE OF A PENABID PRAWN PARAPENAEOPSIS HARDWICKII (MIERS) - Nagabhushanam, R; Kulkarni, G K (Indian Journal of Fisheries, 2011)
Monthly records of female P. hardwickii from September 1977 to August 1978 revealed that they breed throughout the year with high breeding and spawning activity during January-May. The vertebrate male steroid hormones, testo^ sterone propionate and testosterone acetate have inhibitory influence on the ovarian maturation, whereas the aqueous extract of AG alsio blocked the Ovarian growth, but masculiniziation of the ovary was not observed. Eyestalk ablation, did not influence the spawning activity and the quality of eggs produced.